2017
DOI: 10.1186/s12944-017-0625-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and atherosclerosis

Abstract: Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death and it has been confirmed that increased low density lipoprotein cholesterol (LDL-C) is an independent risk factor for atherosclerosis. Recently, the increasing evidence has showed that hypertriglyceridemia is associated with incremental ASCVD risk. But the proatherogenic mechanism of triglyceride (TG) remains unclear. Therefore, this article focuses on the clinical studies and proatherogenic mechanism related to hypertriglyceridemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 85 publications
(107 reference statements)
1
155
0
7
Order By: Relevance
“…Age is known as the dominant cardiovascular disease (CVD) risk factor due to dyslipidaemia in both men and women older than 65 years, as compared to younger individuals [16]. Further, elevated triglycerides (Tg) and very low density level (VLDL) cholesterol levels have been associated with subclinical atherosclerosis and dubbed as independent risk factors for CVD [17]. Several large studies suggest that hypertriglyceridemia is related to increased levels of remnant lipoproteins in promoting atherogenesis [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Age is known as the dominant cardiovascular disease (CVD) risk factor due to dyslipidaemia in both men and women older than 65 years, as compared to younger individuals [16]. Further, elevated triglycerides (Tg) and very low density level (VLDL) cholesterol levels have been associated with subclinical atherosclerosis and dubbed as independent risk factors for CVD [17]. Several large studies suggest that hypertriglyceridemia is related to increased levels of remnant lipoproteins in promoting atherogenesis [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a complicated process involving many mechanisms, such as in ammation, lipid accumulation, and insulin resistance. Chronic in ammation plays a key role in atherosclerosis, and lipoprotein cholesterol accumulation and insulin resistance promote in ammation and the formation of atherosclerotic plaques [13][14][15] . In this study, the main nding was that the AIP, TyG index and MLR were independent risk factors for subclinical CAD.…”
Section: Discussionmentioning
confidence: 99%
“…For the past few years, the research on ectopic fat obesity has gradually increased, it has been found that ectopic fat obesity is an important risk factor for a variety of cardiovascular diseases and type 2 diabetes [7,[15][16][17], while the status of TG has been gradually improved in the cardiovascular and endocrine fields [11,[19][20][21], but there is no clear standard for the evaluation of ectopic fat obesity at present. In this study, after adjusting covariates, it is confirmed that TG is related to ectopic fat obesity (OR:1.55,95%CI:1.41-1.69,p<0.00001), and the risk of ectopic fat obesity in the higher TG group (≥1.118mmol/l) was 3.16 times higher (OR:3.16,95%CI:2.45-4.07,p<0.00001, P for trend<0.00001) than that in the lower TG group (≤0.497mmol/l).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that there is a close relationship between ectopic fat obesity and dyslipidemia, diabetes and cardiovascular disease [7,[15][16][17]. Søndergaard E et al have pointed out that the storage of Triglycerides (TG) in different tissues may lead to ectopic fat accumulation and contribute to the progression of type 2 diabetes [18], in the cardiovascular field, the relationship between TG and a variety of cardiovascular diseases has a similar positive correlation [19][20][21]. At present, there is little research data on the relationship between TG and the risk of ectopic fat obesity, in the guidelines, there are no clear instructions of the treatment of ectopic fat obesity for the management of blood lipids.…”
Section: Introductionmentioning
confidence: 99%